EFEKTIVITAS STRATEGI PELAKSANAAN BELAJAR MENGAJAR DI SMA N 3 PEKANBARU - Yosifa Syafitri; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The effectiveness of teaching and learning as well as the state is right on target in implementing the learning process, so that the goal can be achieved by either. Issues raised is how the effectiveness of teaching and learning implementation strategy at SMA N 3 Pekanbaru. This research aims to determine the effectiveness of teaching and learning implementation strategy at SMA N 3 Pekanbaru. This is adescriptive qualitative study which gives a clear and detailed illustration based on the facts was found in the observation.Theory used in this study Organizational Effectiveness from Gibson in Tangkilisan (2005). interpretes the factors that affect one is the effectiveness of a teaching and learning implementation strategy at SMA N 3 Pekanbaru. Collecting data use observation and interview technique. Technique analysis is descriptive qualitative.After research had been done we found that that the implementation of the teaching is done in SMA N 3 Pekanbaru has been accomplished back in post-disaster and running poorly due to factors that affect the implementation of teaching and learning in SMA N 3 Pekanbaru, this is the availability of budget and availability of facilities are minimal and hinder the implementation of learning teach.Keyword: effectiveness, effectiveness of the strategy, the implementation of teaching and learning